Insentif Ekonomi dalam Penggunaan Lahan (Land Use) Kawasan Lindung di Kawasan Bandung Utara (Incentive of Economy for Land Use in The North Bandung Area) - Endang Hernawan; Hariadi Kartodiharjo; Dudung Darusman; Sudarsono Soedomo (Institut Pertanian Bogor (IPB University), 2009)
West Javanese Province Goverment has decided to provide 45% of West Java area as conservation and protection area. One of the area is North Bandung Area (KBU: Kawasan Bandung Utara). This paper proposed the used of two economic instrument, namely PDR (purchase development right) and PES (payment environment service) in managing the KBU. The paper shows that the use of PDR by ignoring the price of the land would give a hydrological benefit to the people in urban fringe area, rural fringe area, and rural area in the netx 20 years. Meanwhile, the use of PES intruments with incentive application to plant out tree at estate conservation (both forest and non forest land) would provide benefit for minimum 24 years renting period. Further, the analysis shows that the PDR and PES implementation at 4 regencies/city government at KBU should be considered as a good prospect, even though seeing from the finances aspect of APBD, the prospect was still less than the target. Therefore, continous finance policy support at the regencies/city government at that KBU which aimed to provide environmental protection and agricultural farm (pro-environmental budgeting policy) should be considered as emergency needs.Keywords: conservation area, land use, economic incentive, PDR, PESs